STRATEGI BERTAHAN HIDUP PETANI KECIL DI DESA SINDETLAMI KECAMATAN BESUK KABUPATEN PROBOLINGGO - Zainal Abidin; Sri Wahyuni (JURNAL PENDIDIKAN EKONOMI: Jurnal Ilmiah Ilmu Pendidikan, Ilmu Ekonomi dan Ilmu Sosial, 2015)
The research is descriptive qualitative aims to describe survival strategy of small farmers in the village sindetlami besuk sub-district probolinggo district. The determination of the place research using methods purposive the area. A subject of study in this experiment using a snowball that small farmers in rural district sindetlami visit in probolinggo. Data collection in this study using a method of in-depth interviews , observation or observation , and documents .Analysis of data used namely the reduction of data, presentation of ( display ) data , verification or conclusion .Based on the results of research , that small farmers in the village sindetlami classified as poor because of income received from the farm is not enough to meet all their family needs .Poverty makes small farmers applying survival strategy to stay could live. There are 3 strategies which is small farmers to remain active, is a living, the passive and the strategy.A small farmers are actively conducted by seeking side occupation, family members to work and optimize resources we have.The strategy is that small farmers do that by applying a frugal lifestyle. Strategy tissue done small farmers are requesting assistance to social networking they have, both the formal and informal network as neighbors, to borrow money or fiduciary to the bank.